Scientific heritage of the Ural architectural school - Tarasova, Irina; Shipitsyna, Olga (project baikal, 2025)
The article substantiates the necessity of studying the scientific heritage of the Ural architectural school through the lens of the research carried out by the founders of the scientific school of history and theory of architecture N. S. Alferov and A. E. Korotkovsky. In the process of generalisation of the authors’ published historical and theoretical works the main directions of their scientific research were defined. A comprehensive presentation of the variety of scientific studies made by Ural researchers, architects and teachers N. S. Alferov and A. E. Korotkovsky serves as the basis for the formation of a strategic vision of architectural research development at the Ural State University of Architecture and Art.
Keywords: architecture; scientific heritage; scientific research; Ural architectural school; N. S. Alferov; A. E. Korotkovsky